2018
DOI: 10.1093/biolinnean/bly095
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regime drives a latitudinal gradient in morphology and life history in a livebearing fish

Abstract: Within-species diversity is often driven by changing selective regimes along environmental gradients. Here, we provide a direct test of the environmental factors underlying phenotypic diversity across the wide native distribution of eastern mosquitofish (Gambusia holbrooki). We investigated life-history and body-shape divergence (including multiple measures of body size) across more than 14 degrees of latitude in North America, and used Akaike's information criterion-based model selection to determine the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 98 publications
6
33
0
Order By: Relevance
“…At first sight, this result seems to provide support for direct climate‐effects, for instance, via female solicitation of MP to increase genetic variation and/or quality of their offspring under harsh (northern) conditions (Table ). However, path analysis suggested that climatic effects were mainly indirect, mediated by altered life‐history traits, both latitude‐dependent (Ouyang et al, ; Riesch et al, ) and ‐independent. Both types of analyses, however, received relatively low statistical support.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At first sight, this result seems to provide support for direct climate‐effects, for instance, via female solicitation of MP to increase genetic variation and/or quality of their offspring under harsh (northern) conditions (Table ). However, path analysis suggested that climatic effects were mainly indirect, mediated by altered life‐history traits, both latitude‐dependent (Ouyang et al, ; Riesch et al, ) and ‐independent. Both types of analyses, however, received relatively low statistical support.…”
Section: Discussionmentioning
confidence: 99%
“…Northern populations are subject to higher overwinter mortality than southern ones (Cheng et al, ), leading to lower population densities and female‐biased sex ratios, at least at the beginning of the reproductive season (Zulian, Bisazza, & Marin, ). While mosquitofish males are, on average, larger at higher latitudes (Ouyang et al, ; Riesch et al, ), some males can achieve sexual maturity at particularly small body sizes under these conditions (Zulian et al, ; see also Borowsky, for Xiphophorus variatus ), and smaller males are more efficient in sneaky copulations, being more manoeuvrable and more difficult to spot by females (Pilastroet al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations